Ensuring Legal Protection for Halal Product Consumers in Indonesia’s Marketplaces: Shariah Compliance and Regulatory Gaps - Khasanah, Karimatul; Salleh, Mohd Mahyeddin Mohd (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
This article critically examines the extent to which Indonesia’s leading marketplaces, i.e., Shopee, Tokopedia, and Lazada, uphold legal protections for consumers of halal products. Applying a juridical-empirical approach, the study explores the implementation of Law No. 33 of 2014 on Halal Product Guarantee and Law No. 8 of 1999 on Consumer Protection, focusing on the right to truthful product information and the legal validity of halal claims in digital marketplaces. Findings indicate a persistent regulatory gap between statutory mandates and actual marketplace practices: halal labelling is largely self-declared by sellers and rarely subjected to verification or certification enforcement by platforms. While these platforms comply with general consumer protection standards, they fail to ensure the specific legal obligations concerning halal authenticity as declared partially by the seller. Empirical evidence drawn from platform policies and consumer experiences underscores the urgent need for a more integrated regulatory framework involving government halal authorities, certification bodies, and digital marketplace operators. This study contributes to the broader discourse on digital consumer rights in Muslim-majority contexts and proposes actionable policy recommendations to strengthen halal assurance mechanisms in Indonesia’s digital economy.